The Impact of Learning Technology on Cognitive Abilities: Exploring Digital Media Preferences of Indonesian Language Education Students - Restu Bias Primandhika; Ade Hikmat; Imam Safii; Aurelia Sakti Yani (Universitas Muhammadiyah Malang, 2025)
Digital learning transformation has created significant opportunities for developing instructional media that support students’ metacognitive abilities, particularly in the Indonesian Language Education Study Program. This study aims to identify students’ preferences of digital learning media and their impact on learning habits and comprehension gaps. This research employed a mixed-method approach with a sequential explanatory design, involving 123 Indonesian Language Education students from various semesters. Data were collected through quantitative surveys and In-Depth Interviews (IDI) to gain deeper insights. The results revealed that most students preferred digital media (77.24%) over conventional media (22.76%). Visual learning styles dominated (36.59%), with video platforms being the most favoured (32.52%). Correlation analysis showed a significant relationship between the frequency of digital media use and the reduction of comprehension gaps (r = 0.181; p = 0.046), although it was not significant for learning habits. The result of IDI highlights the need for collaborative features, gamification, better journal access, and more relevant support for Indonesian language learning. Data triangulation confirmed that digital media preferences contribute to reducing comprehension gaps, although they do not fully influence learning habits. This study recommends developing interactive and contextual digital learning media by integrating features that support active, collaborative, and based on local culture to strengthen students’ understanding in Indonesian language courses.